2016
DOI: 10.4236/health.2016.815162
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Natural Compound Made of <i>Ecklonia bicyclis</i> Seaweed, <i>Tribulus terrestris</i> and Water-Soluble Chitosan Oligosaccharide, in Male Sexual Asthenia with Mild or Mild-Moderate Erectile Dysfunction and Serum Testosterone Levels at the Lower Limit of Normal

Abstract: Objectives: to evaluate the effectiveness of a natural compound made of Ecklonia bicyclis Seaweed, Tribulus terrestris and water-soluble chitosan oligosaccharide, in the male sexual asthenia with mild or mild-moderate erectile dysfunction and serum testosterone levels between 280 and 350 ng/dl. Materials and Methods: 84 male patients affected by reduced libido and serum testosterone levels at the lower limit of normal, were recruited. We have separated patients in three different age groups: group A (18-45 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Besides, Tribulus terrestris has an effect on erectile function due to its ability to activate the neuronal NO synthase pathways that act at the endothelial level of the corpora cavernosa [20]. Some authors have reported that Tribulus terrestris also increases the serum levels of total testosterone [21]. However, evidence is not converging.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, Tribulus terrestris has an effect on erectile function due to its ability to activate the neuronal NO synthase pathways that act at the endothelial level of the corpora cavernosa [20]. Some authors have reported that Tribulus terrestris also increases the serum levels of total testosterone [21]. However, evidence is not converging.…”
Section: Discussionmentioning
confidence: 99%
“…However, most plant compounds considered endowed by positive effects in the treatment of erectile dysfunction have been investigated only in vitro and/or in vivo models. Few plant compounds (e.g., Crocus sativus L. [21], Tribulus terrestris [22], Panax ginseng [23][24][25] have been tested in humans affected by this syndrome. Among these, the most investigated is P. ginseng, which has been evaluated either as a single agent [23,24] or in combination with M. oleifera and rutin [25] in clinical trials with promising results.…”
Section: Introductionmentioning
confidence: 99%